The process of bubble formation in the hot isostatic pressing treated, doped molybdenum wire - Choi, J.; Lee, J.-H.; Moon, I.-H.; Choi, H.S. (Springer-Verlag, 1990)
Entrapped materials in the bubbles formed in the K- and Si-doped and hot isostatically pressed molybdenum wire were examined by means of scanning electron microscopy (SEM) with energy dispersive X-ray (EDX) spectroscopy. Solidified particles entrapped in the bubbles were identified as Al-K-Si leucite-type oxide. After reheating these solidified particles at 1900 °C for 5 minutes under atmospheric pressure, however, a portion of the particle was homogeneously volatilized. The remainder was identified as an Al-K-Si mullite-type oxide. Therefore, it can be concluded that the added dopants form a single phase upon annealing, and the formation of bubbles in the doped molybdenum wire is due to volatilization of Al-K-Si oxides, not pure elements constituting the oxides. ？ 1990 The Metallurgical of Society of AIME.